COOPERATIVE LEARNING STAD ONLINE TO UPGRADE STUDENTS’ ABILITY IN UNDERSTANDING SIMPLE PRESENT TENSE IN A DESCRIPTIVE TEXT - Netty Meiderwati Pulungan (Jurnal Education and Development, 2021)
This study aimed to upgrade students’ ability in understanding simple present tense in a descriptive text by the implementation of Cooperative STAD through online learning in Kelas VII-1 in SMP Negeri 1 Padangsidimpuan. This study is a classroom action research did online in two cycles with 24 participants, and the researcher herself involved as a participant-observer. ingThis is a qualitative study because investigated the value of teaching writing, and concentrated mainly on finding out how the teaching steps of a Cooperative STAD can upgrade students’ understanding of simple present tense in a descriptive text. The following are the results of the study. The implementation of STAD by online learning significant to improve students in ability in mastering simple present tenses uses in a descriptive text. Cooperative learning activities creates pleasurable atmosphere in a teaching and learning. The enjoyable and non-threatening atmosphere and interesting media make learning process more meaningful. The opportunity to ask and answer questions, work in a group or pair, give feedback, and correct their works trained students’ confident in learning. However, implementing Cooperative STAD online consumes time. Cooperative learning also tend to make in conductive teaching learning process. Relevant studies regarding the issues need for conducting for better and satisfying finding.